The Stepping Threshold Test for assessing reactive balance discriminates between older adult fallers and non-fallers - Hezel, Natalie; Buchner, Theresa; Becker, Clemens; Bauer, Jürgen M.; Sloot, Lizeth H.; Steib, Simon; Werner, Christian (Frontiers in sports and active living, 2024)
Introduction The ability to respond effectively to external perturbations is crucial for avoiding falls. The Stepping Threshold Test (STT) has been developed to assess this reactive balance, but its ability to discriminate between fallers and non-fallers is still unsubstantiated. This study aimed to evaluate the discriminant validity of the STT in distinguishing fallers and non-fallers and its convergent validity. Methods Thirty-six older adults (age = 80 ± 5 years), with 13 (36%) of them reporting a fall history in the past year, completed the STT on a perturbation treadmill. They received surface perturbations of progressively increasing magnitude while standing. Single- and multiple-step thresholds were assessed using an all-step count evaluation (STT-ACE), and a direction-sensitive evaluation strategy (STT-DSE). Receiver operating characteristics and area under the curves (AUC) were analyzed to evaluate the discriminative accuracy. Convergent validity was explored by 13 hypothesized associations with other mobility, psychological, and cognitive assessments. Results Fallers and non-fallers significantly differed in the STT-DSE (p = 0.033), but not in the STT-ACE or other commonly used mobility assessments. Acceptable discriminative accuracy was obtained for the STT-DSE (AUC = 0.72), but not for the STT-ACE and other mobility assessments (AUC = 0.53-0.68). Twelve (92%) associations were consistent with our hypotheses for the STT-DSE, and ten (77%) for the STT-ACE. Conclusion Our findings provide preliminary evidence that the STT, when using the STT-DSE, may discriminate between older adult fallers and non-fallers. The STT appears to be a valid tool for assessing reactive balance, with its STT-DSE being recommended due to its better discriminant and convergent validity compared to the STT-ACE.
Gesehen am 26.11.2024